Spiritual Care Competence among Malaysian Staff Nurses - Abusafia, Ali H.; Mamat, Zakira; Rasudin, Nur Syahmina; Bakar, Mujahid; Ismail, Rohani (Nurse Media Journal of Nursing, 2021)
Background: Perceptions and levels of understanding of spiritual care vary among nurses, which may affect their competency to meet the patient’s spiritual needs. Therefore, determining nurses' perception of spiritual care is the first important step in addressing the spiritual needs of patients, and may also help nursing management in developing spiritual care education and training programs.Purpose: This study aimed to assess the competence of Malaysian nurses toward providing spiritual care and identify the relationship between nurses’ spiritual care competence and their sociodemographic factors. Methods: This study employed a cross-sectional design to assess nurses' competence in spiritual care by using a simple random sampling method which involved 271 staff nurses from a public hospital in Northeast of Peninsular Malaysia. Spiritual care competence scale in Bahasa Malaysia version was used for data collection. Data analysis was performed using descriptive (frequency, percent, mean, standard deviation) and inferential (Chi-square and Pearson’s correlation test) statistics.Results: This study showed that 69.7% of staff nurses had an average level of competence toward providing spiritual care for the patients (M=95.44, SD=4.34). The highest mean difference among the domains was personal support and patients counseling (MD=5.789), while the lowest mean difference was assessment and implementation of spiritual care (MD=1.258). Furthermore, there was no significant relationship between spiritual care competence and sociodemographic factors (gender, age, marital status, educational level, nurses' experience, race, religion, and previous participation in training spiritual care programs).Conclusion: The majority of nurses have an average level of competence toward providing spiritual care. There is no significant relationship between nurses’ spiritual care competence and sociodemographic factors.